COMPLEX SUPPLEMENTS FROM RENEWABLE RAW MATERIALS FOR SPECIALIZED NUTRITION OF SPORTSMEN - An'shakova V.V.; Stepanova A.V.; Uvarov D.M. (Техника и технология пищевых производств, 2017)
Mechanicochemical technology has been developed for obtaining highly efficient solid phase biological complexes (solvent- free) in single process step. Presented are the results of evaluation of the effect of mechanical activation of complexes based on lichen thalli and a small amount of Rhodiola rosea on the content of low molecular weight antioxidants for creating food supplements based on them. А qualitative analysis for determination of flavonoids and of the total content of low molecular weight antioxidants has been conducted with spectrophotometry based on the ability of ferric chloride (III) to oxidize low molecular weight antioxidants. It has been found that the process of mechanical activation of components is accompanied by the destruction of cell walls and changing of chemical composition of plant raw materials due to rupture of a number of chemical bonds thus forming weak intermolecular interactions which lead to the formation of the complex of hydro- and lipophilic nature, thus creating optimum conditions for the diffusion process resulting in 5-10 times increase of bioavailability of biologically active substances. It is shown that the content of low molecular weight antioxidants increases with mechanical activation of the feedstock, as well as with the increase of Lichen : Rhodiola rosea proportions in biocomplexes. The efficiency of using of a complex dietary supplement during intensive physical activity has been investigated.